Vegetation outlines of two active rock glaciers with contrasting lithology - D. Tampucci; F. Mangili; M. Caccianiga; G. Boffa; M. Gobbi (2015)
Rock glaciers are periglacial landforms consisting of coarse debris with interstitial ice or ice core, characterized by creeping due to ice deformation. These landforms are drawing the attention of plant ecologist as harsh habitats and potential refugia in the global change context. Our aim was to describe the vegetation outlines of two active rock glaciers of the Ortles-Cevedale Massif (Central Italian Alps) on different substrates (silicate and carbonate) and compare them with the neighboring stable slopes and scree slopes. Two hypotheses were tested: 1) rock glaciers differ from the surrounding landforms for the presence of cold-adapted plant communities; 2) rock glacier plant communities indicate similar microclimatic conditions in spite of the contrasting lithology. Data were collected by phytosociological method performing 80 relevés of 25 m². Plant communities were compared by a cluster analysis based on the presence/absence species matrix and species relative frequencies for each landform were calculated. The cluster analysis separated first for all the two sites; afterwards, the landforms were differently discerned each other depending on the site. Despite the remarkable floristic differences due to the substrate, the vegetation of both rock glaciers suggest a general adjustment to cold-moist microclimate and long-lasting snow cover, differentiating more or less evidently from the adjacent scree slopes and enhancing the survival of nival entities at the elevation of alpine grasslands.